2023
DOI: 10.1101/2023.03.22.23287607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rates and predictors of data and code sharing in the medical and health sciences: A systematic review with meta-analysis of individual participant data

Abstract: Objectives: Many meta-research studies have investigated rates and predictors of data and code sharing in medicine. However, most of these studies have been narrow in scope and modest in size. We aimed to synthesise the findings of this body of research to provide an accurate picture of how common data and code sharing is, how this frequency has changed over time, and what factors are associated with sharing. Design: Systematic review with meta-analysis of individual participant data (IPD) from meta-research s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 172 publications
0
2
0
Order By: Relevance
“…Some studies included an observational assessment of the child, EMA assessment data, such as written or electronic diaries, app-based data, or physiological sensors, or interviewer assessments of the child, their family, or environment. There is an increasing expectation for researchers to share the data they report on (Mello et al, 2013) although sharing also raises concerns around informed consent, data management, data dissemination, and validation of research contributions (Alter & Vardigan, 2015) and has logistical and cost implications (Hamilton et al, 2023). Many studies did not report on data accessibility and of those that did, the majority reported restricted access-mainly due to data privacy-or required application and/or payment for data access.…”
Section: Information Sources and Contentmentioning
confidence: 99%
“…Some studies included an observational assessment of the child, EMA assessment data, such as written or electronic diaries, app-based data, or physiological sensors, or interviewer assessments of the child, their family, or environment. There is an increasing expectation for researchers to share the data they report on (Mello et al, 2013) although sharing also raises concerns around informed consent, data management, data dissemination, and validation of research contributions (Alter & Vardigan, 2015) and has logistical and cost implications (Hamilton et al, 2023). Many studies did not report on data accessibility and of those that did, the majority reported restricted access-mainly due to data privacy-or required application and/or payment for data access.…”
Section: Information Sources and Contentmentioning
confidence: 99%
“…Less attention has been paid to what the key contributors to, and ultimate consumers of medical research -patients -think of these practices [11,12]. Furthermore, research on this topic has focussed on certain data types (e.g., omics data [13,14]), study designs for which public sharing of data is not routine (e.g., clinical trials [12,15,16]) or specific cancer types (e.g., breast cancer [4]). Therefore, this study aims to contextualise and build upon previous research into public opinions on data sharing by engaging Australians affected by cancer and characterising their views on the sharing of deidentified research data with third parties, including the public.…”
mentioning
confidence: 99%